Influence of Vitamin D and IgE Levels on Recurrent wheezy Chest in Children under Two Years of Age; A Hospital-Based Case-Control Study - Mohammed Hasan Saeed; Kawes Omer Zangana (Advanced Medical Journal)
Background and objectives: Wheezing is a common presenting symptom of respiratory disease in children. Thirty percent of children experience at least one acute wheezing illness before the age of three years, and it is one of the most common causes of morbidity and mortality, the most frequent causes of wheezing are bronchiolitis and asthma. Recurrent wheezing has significant morbidity. It is estimated that about one third of children manifest symptoms during the first years of life. Vitamin D is fat soluble and its role is helping growth of bone and function of immunity is crucial. IgE has essential role in type I hypersensitivity reaction like allergic asthma, allergic rhinitis and others. Our study aimed to estimate serum vitamin D and IgE level in infants and children less than 2 years of age with recurrent wheeze.